Lipid biosynthesis in yeasts: A comparison of the lipid biosynthetic pathway between the model nonoleaginous yeast Saccharomyces cerevisiae and the model oleaginous yeast Yarrowia lipolytica. Issue 3 (7th July 2016) - Fakas, Stylianos
Abstract : Lipid biosynthesis and its regulation have been studied mostly in the nonoleaginous yeast Saccharomyces cerevisiae that serves as a model for eukaryotic cells. On the other hand, the yeast Yarrowia lipolytica has been put forward as a model for oleaginous microorganisms because its genetics is known and tools for its genetic manipulation are becoming increasingly available. A comparison of the lipid biosynthetic pathways that function in these two microorganisms shows many similarities in key biosynthetic and regulatory steps. An example is the enzyme phosphatidic acid phosphatase that controls the synthesis of triacylglycerol (TAG) in both yeasts. Controlling the TAG synthesis is crucial for metabolic engineering efforts that aim to increase the production of microbial lipids (i.e. single cell oils) because TAG comprises the final product of these processes. At the same time the comparison reveals fundamental differences (e.g. in the generation of acetyl‐CoA for lipid biosynthesis) stemming from the oleaginous nature of Y. lipolytica . These differences warranty more studies in Y. lipolytica where the biochemistry and molecular biology of oleaginicity can be further explored.